Neurobehavior and neuron damage following prolonged exposure of silver nanoparticles with/without polyvinylpyrrolidone coating in Caenorhabditis elegans. Issue 12 (16th May 2021) - Zhang, Wenli; Li, Wenhua; Li, Jiangyan; Chang, Xiaoru; Niu, Shuyan; Wu, Tianshu; Kong, Lu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract: Silver nanoparticles (AgNPs) have become widespread in the environment with increasing industrial applications. But the studies about their potential health risks are far from enough, especially in neurotoxic effects. This study aimed to investigate the neurotoxic effects of longer‐term exposure (prolonged exposure for 48 h and chronic exposure for 6 days) of 20nm AgNPs with/without polyvinylpyrrolidone (PVP) coating at low concentrations (0.01–10 mg·L −1 ) to Caenorhabditis elegans . The results suggested that exposure to AgNPs induced damage to nematode survival, with the longest and relative average life span reduced. Exposure to AgNPs caused neurotoxicity on locomotion behaviors (head thrashes, body bends, pharyngeal pumping frequency, and defecation interval) and sensory perception behaviors (chemotaxis assay and thermotaxis assay), as well as impaired dopaminergic, GABAergic, and cholinergic neurons, except for glutamatergic, based on the alters fluorescence intensity, in a dose‐ and time‐dependent manner. Further investigations suggested that the low‐dose AgNPs (0.01–0.1 mg·L −1 ) exposure raises receptors of GABAergic and dopamine in C. elegans at the genetic level, whereas opposite results were observed at higher doses (1–10 mg·L −1 ), which implied that AgNPs could cause neurotoxicity by impairing neurotransmitter delivery. The PVP‐AgNPs could cause a higher fatality rate and neurotoxicity at the same dose. Notably, AgNPs did not cause any deleterious effect on nematodes at the lowest dose of 0.01 mg·L −1 . In general, these results suggested that AgNPs possess the neurotoxic potential in C. elegans and provided useful information to understand the neurotoxicity of AgNPs, which would offer an inspiring perspective on the safe application. Abstract : In this study, C. elegans was used as a model to evaluate the neurotoxicity of longer‐term exposure of 20nm AgNPs with/without PVP coating at low concentrations. The decreased survival rate and damaged neurobehavior, as well as impaired neurons and neurotransmitters in C. elegans, were observed. The PVP‐AgNPs caused a higher fatality rate and neurotoxicity. The results indicated that AgNPs caused neurotoxicity on nematodes at the doses over 0.1 mg·L −1, which provided clues for the safe application of AgNPs.